Adherence to self‐care behavior and glycemic effects using structured education. Issue 6 (17th April 2015) - Yang, Yi‐Sun; Wu, Yueh‐Chu; Lu, Ying‐Li; Kornelius, Edy; Lin, Yu‐Tze; Chen, Yu‐Ju; Li, Ching‐Lu; Hsiao, Hui‐Wen; Peng, Chiung‐Huei; Huang, Chien‐Ning
Abstract Aims/Introduction The purpose of the present study was to examine glycemic control in suboptimally controlled type 2 diabetes provided by a structured education group using the Diabetes Conversation Map™ (CM™) vs usual care in a university‐based hospital primary care clinic. Materials and Methods This was a randomized, pragmatic clinical trial. Patients with type 2 diabetes were randomly assigned to structured education or usual care groups. The primary outcome was the difference in the mean change of glycated hemoglobin (HbA1c) from baseline to 12 months. Secondary outcomes included the percentage achieving therapeutic HbA1c goal and self‐behavioral changes. Results A total of 245 patients were randomly assigned to two groups (CM™ group n = 121; usual care group, n = 116). The absolute reduction of HbA1c was significantly greater in the CM™ group at 3 and 6 months (Δ = −0.59% and Δ = −1.13%, P < 0.01), but the difference was no longer statistically significant at 9 and 12 months (Δ = −0.43% and Δ = −0.49%), based on an intention‐to‐treat analysis. A per‐protocol analysis showed the significant change was maintained at 12 months (Δ = −0.67%). In the intervention group, greater percentages of patients achieved their American Association of Diabetes Educators Self‐Care Behaviours™ framework (AADE7) behavioral goals at 3 months, in particular being active, problem‐solving, reducing risk and health coping. Conclusions In type 2 diabetic patients with suboptimally controlled glucose, there were greater improvements in glucose control and self‐care behavioral goals in those who underwent the CM™ education program compared with outcomes achieved in patients receiving usual care.